Tradisi dan Budaya Simpan Pinjam Perempan Berbasis Mudharabah Pada Jamaah di Kecamatan Tegaldlimo Kabupaten Banyuwangi - Sofi Faiqotul Hikmah (Universitas KH. MUkhtar Syafaat (UIMSYA) Blokagung Banyuwangi, 2024)
This research has three objectives, namely: 1) To analyze how the tradition and culture of Women’s Savings and Loans is implemented in Purwoasri Village, 2) To analyze what the contribution of the Women’s Savings and Loans program is to the economy of the people of Purwoasri Village, and 3) To analyze how Islamic law views this mudharabah-based SPP transaction for pilgrims in the Tegaldlimo District, Banyuwangi Regency. The research method that the author uses is descriptive qualitative. The results of the study show that: 1) The implementation of the Women’s Savings and Loans begins with forming a group, submitting data on the name of the group, survey, submits a fund to BUMDESMA, legality, disbursement, repayment, and payment of fees Women’s Savings and Loans members. 2) The contribution are: As additional business capital, encouraging institutional strengthening, helping to meet consumptive needs, maintaining harmony among congregation members, increasing village income, and reducing poverty and unemployment. 3) Islamic law views the implementation of Women’s Savings and Loans, that Women’s Savings and Loans transactions use an interest system, not profit sharing. The implementation of the Women’s Savings and Loans is not al-Qard, because it is not in accordance with the criteria stated in the DSN Fatwa regarding Qard. SPP has not fully used the mudharabah contract because it is still 73% with the mudharabah contract criteria.